Student Disciplinary Practices in a Boarding School Environment: A Sociological Review - Noviani, Dwi; Azkar, Muh. (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This study aims to explore the practice of disciplining students in a boarding school environment through a sociological approach using qualitative case study research methods. Boarding schools are formal educational institutions that systematically plan guidance, teaching, and training for students with the aim that students can develop according to their potential. The qualitative research method was chosen to explore in depth the social dynamics in boarding schools. Data were collected through interviews with students, educators, dormitory heads, and dormitory coaches, participatory observation, and document analysis related to discipline policies. The results of this study through sociological research, found that discipline occurs in boarding schools through the active role played by educators, dormitory heads, and dormitory coaches in enforcing the rules of discipline to form discipline in students. Disciplinary practices in boarding schools are carried out using two disciplinary mechanisms, namely supervision through disciplinary rules and sanctioning students. The implications of this article can provide insights for the development of disciplinary methods that are more effective and under the social needs of students.